Biotechnology: Applications of Tissue Engineering in the regeneration of human organs and tissues - Review (Research, Society and Development, 2023)
Tissue engineering is a promising field in biotechnology that involves the combination of cells, biomaterials, and growth factors to create structures capable of replacing or regenerating damaged tissues. The growing demand for solutions due to organ scarcity and injuries has driven multidisciplinary approaches in the development of biomaterials for this purpose. Therefore, the objective of this study is to conduct a literature review by analyzing articles on the evolution of tissue engineering, its techniques, and how it is applied in current medicine. The conclusion drawn is that, despite multiple challenges in tissue engineering modernization, such as creating functional blood vessels and ethical issues, with investments in research and the use of appropriate regulations, bioengineering has revolutionized regenerative medicine through techniques like 3D printing, the use of scaffolds, and bioimpressions. This has led to a reduction in transplant waiting lists and improved prospects for patients seeking medical care.